ANALISIS PENGARUH BRAND IMAGE, SERVICE QUALITY, DAN PERCEIVED VALUE TERHADAP KEPUASAN PELANGGAN YANG BERDAMPAK PADA BRAND LOYALTY (Studi pada Pengguna Kartu Prabayar Indosat di Kota Semarang) - Aji, Galih Putro; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2014)
This study aims to determine whether Brand Image, Service Quality, PerceivedValue, Customer Satisfaction which affect the impact on Brand Loyalty Prepaid Card Users Indosat Semarang. This study was conducted by questionnaire to 100 respondents were users of Indosat products obtained using non-probability sampling techniques. This type of sampling is purposive sampling. The population in this study is the consumer who uses the product of PT. Indosat more than 2 years and living in the city of Semarang at least 17 years old. Methods of data analysis in this study are: validity and reliability, the classic assumption test, multiple regression analysis, hypothesis testing with the t test and F test, and test analysis of the coefficient of determination (R2). Based on the analysis of test results, obtained by the regression equation as follows: Y1 = 0,228X1 + 0,614X2 + 0,154X3  and Y2 =   0,953Y1 Brand  Image  Variable  has  the  effect  of  customer  satisfaction  0.228,  then  the variable service quality has the effect of 0.614 to customer satisfaction, and perceived value of 0.154 to influence customer satisfaction. As for the effect of customer satisfaction on brand loyalty 0.953. Testing hypotheses were performed using the t test showed that these variables at the top of the Brand Image (x1), Service Quality (x2), Perceived Value (x3), positive and significant effect on customer satisfaction (y1). Then the Customer Satisfaction (y1) and a significant positive impact on Brand Loyalty (y2). The next test f test conducted showed that the variable Brand Image, Service Quality, Perceived Value feasible to test customer satisfaction variable as the dependent variable, and the variable customer satisfaction as a moderating variable declared eligible for the test variables of brand loyalty. Adjusted R Square indicates that the brand image, service quality and value perseived in explaining variation in the dependent variable of customer satisfaction is96.5% and the remaining 3.5% is influenced by other variables. As for the ability of customer satisfaction in a position as a moderating variable in explaining variation in the dependent variable is the Brand Loyalty is 90.8% and the remaining 9.2% is influenced by other variables.